“Minat, Motif, Tujuan, dan Manfaat Membaca Novel Teenlit Bagi Remaja Jakarta: Studi Resepsi Sastra” - Redyanto Noor (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
The reality of young readers'(Jakarta) receptions of the teenlit novel concerning the motives, purposes, and benefits of reading the teenlit novel explains the social-cultural function of teenlit novel. Teenlit novel as a means of entertainment is able to fulfill the social-cultural function, which is giving spiritually pleasure, to be able to accommodate the horizon-expectations of adolescent readers. Teenlit novel provides entertainment while teaching